SEVERE HYPERTRIGLYCERIDEMIA SUCCESSFULLY TREATED WITH INSULIN INFUSION : A CASE REPORT - Zuki, Rabeah Md; Velaiutham, Shanty; Hui, Khaw Chong; Peng , Sun Choon (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Patients with severe hypertriglyceridemia (HT) are at risk of developing life-threatening acute pancreatitis and cardiovascular disease. There is no standard guideline on managing severe HT in acute settings. Apheresis, heparin and insulin therapy has been utilised and reported. CASE We report a 42-year-old male who was referred to us from private healthcare for severe HT. He has hypertension and dyslipidaemia for 1 year and was prescribed with atorvastatin and fenofibrate for lipid management. He was only recently diagnosed with diabetes mellitus (DM) with HbA1c of 13%. There was no family history of hyperlipidemia or ischaemic heart disease. He did not have any abdominal pain or chest pain. On examination, there were multiple eruptive xanthomatas over the extensor surface of both elbows and knees and at the Achilles tendon area. Laboratory investigations revealed severe HT with serum triglyceride (TG) of 44.6 mmol/L and total cholesterol of 19.6 mmol/L. His blood exhibited thick and milky supernatant. Serum amylase was not elevated. Liver function test was normal. In view of severe HT, the patient was admitted and variable rate insulin infusion was started. His TG decreased progressively to 22.7 mmol/L by day 2 of admission and finally to 10.7 mmol/L by day 6 of admission. He was discharged on statin and fenofibrate together with his antihyperglycaemic medications. Screening for his family members was also done. Although there was no family history, we planned for genetic study for him soon. CONCLUSION This case showed successful therapy for severe HT with insulin infusion. It is non-invasive and cost-effective treatment option for severe HT. Rapid reduction of high TG is important to reduce risk of pancreatitis.